Physical Safety A Matter of Balancing Responsibilities - WRR (WRR Publications, 2012)
Physical safety is a core task of government. It is neither surprising nor unreasonable for government to be held accountable for hazardous substances, for food safety, for flood protection, for the spread of infectious diseases, or for the risks involved in new technologies. In 2011 the Dutch Ministry of the Interior and Kingdom Relations asked the Scientific Council for Government Policy (wrr) to investigate the scope for the development of a generic risk policy in relation to physical safety. Do citizens and businesses take sufficient responsibility for physical safety? Could the government assume a smaller role, and what part could the business community play in this? In this report the WRR argues that in order to answer these questions a distinction needs to be made between incidents, damage, risk and uncertainty. In addition, the wrr recommends that the thinking about responsibility for safety should not be placed in the perspective of a failing government, but that the central focus should be on the ambition of good governance. Finally, the wrr suggests that thinking about safety from the perspective of damage offers a useful framework for thinking through and reassessing the distribution of responsibilities. Responsibility for preventing, limiting and dealing with damage can only be assigned in advance, not retrospectively.